Analisis Yuridis Pelaksanaan Take Over Kredit Pemilikan Rumah (KPR) dalam Perjanjian Jual Beli Rumah di Bawah Tangan - Rian Fauzi Rahman (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to determine the implementation of Take Over in the sale and purchase of houses on credit in Home Ownership Credit, to determine the legal consequences of the implementation of Take Over Home Ownership Credit underhand, and to resolve the settlement of legal problems that occur if Take Over in the sale and purchase of houses on credit is carried out underhand. An ideal agreement that is expected to run and become a trust that will be held by each party. However, in certain conditions, it is often found that the agreement cannot run as it should, so what is done is a shortcut by transferring rights to the object of Home Ownership Credit, namely the house, which is carried out underhand by the debtor to another party before the Home Ownership Credit is paid off without the knowledge of the bank or known to the public as over credit. The implementation mechanism of Take Over Home Ownership Credit normatively does not require a very long time, simply by the customer coming to the bank bringing the requirements that have been determined by the Bank, then after the requirements are approved by the Bank, the application only takes two weeks. And the bank will process the documents before a notary and notarially with the party who will receive the Home Ownership Credit from the applicant. Based on this, the problem that will be studied is the debtor transfer process (Take Over), and what are the legal consequences of the debtor transfer carried out underhand and legal efforts to resolve the problems that arise afterwards. The research conducted is a type of normative legal research. Sources of legal materials include primary legal materials, secondary legal materials and tertiary legal materials. Legal materials obtained in the study were collected through literature studies. The conclusions obtained from the results of the research and discussion that have been carried out are: the agreement between the customer and the Bank, Take Over home ownership credit underhand, and the settlement of the legal consequences of buying and selling a house through Take Over underhand.